Examen especial a los ingresos y gastos del gobierno autónomo descentralizado parroquial rural Cuyuja, cantón Quijos, provincia de Napo, en el periodo 2014. - Tipantiza Espinoza, Mayra Karina (2016)
This was developed as a prerequisite for obtaining the title of Engineer in Accounting and Auditing "Panel to the Income and Expenses of Self-Government Decentralized Rural Cuyuja Parish, Canton Quijos, Napo Province in Period 2014 Review"; and it aims to identify any deficiencies in internal control that makes the institution to control your income and expenses, and later establish the recommendations on administrative management and financial management. The objectives, the methodological process used in the preparation of this work has been developed based on basic and fundamental concepts related to the special examination process, scientific, deductive, inductive methods and techniques used direct observation, interview and survey allowed to detect weaknesses in internal control of the Autonomous Government Decentralized Rural Parish Cuyuja (GADPRC) through the application of questionnaires and assessment of the components of internal control to determine the degree of confidence and risk level; and in the accounting and financial management of the accounts of revenues and expenses by applying special test programs that they enabled the analysis of each component. Narratives bonds to the findings detected in internal control to those detected during the application of special test programs were developed. The results of the research findings by leading evidence related to the wrong registration deposit collected the wrong values, supporting documentation, among others, a situation which leads to adjustments shown in the reporting of results. The final report contains comments, conclusions and recommendations aimed at improving the economic management of the company, the product of the development of this special review was submitted for consideration of the President of GADPR of Cuyuja, which is to follow up on the recommendations.